2009
DOI: 10.2174/1874192400903010152
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and Persistence to Statin Treatment in Patients with Diabetes Receiving Glucose-Lowering Medications 1997- 2006

Abstract: Aims:Since 2001 guidelines recommend statin treatment in most patients with diabetes. We investigated secular changes in initiation and persistence to statin treatment during a 10-year period in a nationwide cohort of patients initiating glucose-lowering medication (GLM).Methods:All Danish citizens 30 years and older who claimed prescriptions of GLM between 1997 and 2006 were identified from nationwide registers of drug dispensing from pharmacies and hospitalizations, and followed until 2006. Statin treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Data from the UK General Practice Research Database showed an increase in statin use from about 5% in 1996 to 63.5% in women and 71.0% in men in 2005,10 which was associated with HRs of mortality of 0.29 in women and 0.34 in men in the first 2 years following diagnosis of diabetes. Similarly, in Denmark, only 7% of patients receiving glucose-lowering medication also received statins in 1997, but this had increased to 62% in 200711; information on mortality in that study is however lacking. In our cohort of older persons with diabetes, the prevalence of statin medication use was 35% overall.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Data from the UK General Practice Research Database showed an increase in statin use from about 5% in 1996 to 63.5% in women and 71.0% in men in 2005,10 which was associated with HRs of mortality of 0.29 in women and 0.34 in men in the first 2 years following diagnosis of diabetes. Similarly, in Denmark, only 7% of patients receiving glucose-lowering medication also received statins in 1997, but this had increased to 62% in 200711; information on mortality in that study is however lacking. In our cohort of older persons with diabetes, the prevalence of statin medication use was 35% overall.…”
Section: Discussionmentioning
confidence: 94%
“…This improvement is possibly a result of better adherence to published clinical guidelines, advocating aggressive multifactorial treatment 9. However, many patients with type 2 diabetes are still not receiving treatment with statin medication 10 11…”
Section: Introductionmentioning
confidence: 99%
“…Since women tend to have infarctions at an older age than men as well as higher rates of comorbidities, the poorer outcomes in women than in men have largely been attributed to these factors; sex has generally not been interpreted as constituting an independent association [17]. Furthermore, Dominguez et al have shown that women with diabetes are not treated less frequently with statins than their male counterparts [18]. Since the above-mentioned study did not reveal a convincing sex-related difference in statin treatment, the explanation of the higher risk for MI in women following initiation of GLM remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Only patients under the age of 40 years, with newly diagnosed type 2 diabetes, and without clinical complications or other CVD risk factors, may be withheld from statin therapy 1. In practice, at least 80% of the patients with diabetes who begin taking a statin seem to have no established CVD 8 9…”
Section: Introductionmentioning
confidence: 99%